2018
DOI: 10.2147/pgpm.s169277
|View full text |Cite|
|
Sign up to set email alerts
|

The impact of <em>ABCB1</em> (rs1045642 and rs4148738) and <em>CES1</em> (rs2244613) gene polymorphisms on dabigatran equilibrium peak concentration in patients after total knee arthroplasty

Abstract: BackgroundNon-vitamin K oral anticoagulants (NOACs) are commonly used for prophylaxis of venous thromboembolism (VTE) in orthopedic patients. Despite known safety and high potency of NOACs, potential interactions of NOACs with genetic polymorphisms are poorly understood. Dabigatran etexilate is one of the most commonly prescribed direct thrombin inhibitors for the prevention of VTE. The objectives of this study were to assess the effect of ABCB1 (rs1045642 and rs4148738) and CES1 (rs2244613) polymorphisms on d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
38
1
9

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 9 publications
6
38
1
9
Order By: Relevance
“…Similarly, some studies found a significant influence of such polymorphism on the pharmacokinetics of antiviral atazanavir and the clinical outcomes of artemether-lumefantrine antimalarial regimen [37], [45] as well as the chemotherapy clinical outcomes in pediatric patients with leukemia [30], [39]. Furthermore, C3435T rs1045642 polymorphism has even been proven to correlate significantly with amlodipine efficacy and safety, patients' blood pressure after kidney transplantation, and the safety of dabigatran as a thrombin inhibitor [40], [42], [43]. Not only associated with pharmacogenomics because of their function as part of cellular defense mechanism, but C3435T polymorphism also has a significant clinical correlation as a predisposition to depressive disorders [28], [34], [38].…”
Section: Resultsmentioning
confidence: 98%
“…Similarly, some studies found a significant influence of such polymorphism on the pharmacokinetics of antiviral atazanavir and the clinical outcomes of artemether-lumefantrine antimalarial regimen [37], [45] as well as the chemotherapy clinical outcomes in pediatric patients with leukemia [30], [39]. Furthermore, C3435T rs1045642 polymorphism has even been proven to correlate significantly with amlodipine efficacy and safety, patients' blood pressure after kidney transplantation, and the safety of dabigatran as a thrombin inhibitor [40], [42], [43]. Not only associated with pharmacogenomics because of their function as part of cellular defense mechanism, but C3435T polymorphism also has a significant clinical correlation as a predisposition to depressive disorders [28], [34], [38].…”
Section: Resultsmentioning
confidence: 98%
“…По результатам четырех исследований [10,13,14,16], включавших 1970 пациентов, носительство аллели С rs2246613 статистически значимо ассоциировано со снижением риска развития любых кровотечений на фоне приема дабигатрана (ОР 0,732, 95%ДИ 0,629-0,851; p<0,001). Тест на гетерогенность не выявил статистически значимых различий между результатами исследований (Q=2,183; p=0,535) (рис.…”
Section: результаты и обсуждениеunclassified
“…Sychev и соавт. [14,15] Эти результаты могут свидетельствовать о перспективе использования данного полиморфизма в качестве генетической детерминанты безопасности дабигатрана, например, при коррекции дозы препарата у пациентов с повышенным риском геморрагических осложнений.…”
Section: результаты и обсуждениеunclassified
“…D. Sychev и соавт. не удалось подтвердить влияния полиморфизма CES1 rs2244613 на пиковую концентрацию дабигатрана у пациентов после тотальной артропластики коленного сустава [61]. К. Мирзаев и соавт.…”
Section: другие ферменты окисленияunclassified
“…В клинических исследованиях D. Sychev и соавт. установили, что генотип TT полиморфизма rs1045642 гена ABCB1 был связан с более высокими пиковыми концентрациями дабигатрана и более высоким риском кровотечения, чем наличие генотипа СС (р<0,008) [61], а также указывают на потенциал фармакогенетического тестирования SNP rs1045642 при назначении амлодипина у пациентов с артериальной гипертензией I-II стадии [65]. Moscow / Москва *¹ [65] Moscow / Москва *² [66] Moscow / Москва [67] Moscow / Москва ³ [68] Laks / Лакцы [22] Dargins / Даргинцы [22] Avars / Аварцы [22] Russians / Русские 4 [69] Nanais / Нанайцы [23] Population / Популяция Prevalence / Распространенность (%) Figure 8.…”
Section: Ihd / ибс [24]unclassified